The trial against Hissène Habré: networked justice and reparations at the Extraordinary African Chambers. Issue 9 (22nd November 2017) - Sperfeldt, Christoph
ABSTRACT: The establishment of the Extraordinary African Chambers to try former Chadian President Hissène Habré has been hailed as a novel form of prosecuting international crimes in Africa. The Court's establishment marked the end of more than two decades of persistent lobbying by a network of victim associations and civil society organisations – a phenomenon that is referred to here as 'networked justice'. This article shows that the characteristics of a network often determine the reach and outcomes of networked justice at local and international levels. In the case of the Habré trial, the network's primary goal of setting an international legal precedent through universal jurisdiction defined the tools and strategies chosen to achieve the goal. This article shows how these dynamics were transposed to the trial against Habré and the reparations phase. The take-up of sexual violence at trial is highlighted as one example of networked justice in action. By returning to Chad, this article considers the potential of reparations as a tool for carrying over effects from an internationalised justice process to the domestic level, and concludes with some observations about the possibilities and limitations of networked justice approaches in stimulating processes of transformation and change at the locations where justice demands originated.